Non-Native Language Questionnaire Usage [Letter] - Durant D (Advances in Medical Education and Practice)
Danielle Durant Addenbrooke’s University Hospital, Cambridge, UKCorrespondence: Danielle Durant, Email Danielle.durant3@nhs.net